2019
DOI: 10.3390/catal9050480
|View full text |Cite
|
Sign up to set email alerts
|

Mild Ammonia Synthesis over Ba-Promoted Ru/MPC Catalysts: Effects of the Ba/Ru Ratio and the Mesoporous Structure

Abstract: A series of novel mesoporous carbon-supported, Ba-promoted, Ru catalysts with Ba/Ru ratios of 0.1–1.6 and a Ru loading of 10 wt% (denoted as 0.1–1.6Ba-10Ru/MPC) were prepared via stepwise impregnation of Ru and Ba precursors on the mesoporous carbon materials. The catalysts were applied to mild ammonia synthesis and compared to reference materials, including an analog of the prepared catalyst with a Ba/Ru ratio of 1.6 and a Ru loading of 10 wt% (denoted as 1.6Ba-10Ru/AC). Characterization by X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…All samples presented a broad peak centered at approximately 640–660 °C. This was ascribed to the thermal instability of AC, which formed gas products such as CH 4 , CO, and CO 2 via the methanation and thermal decomposition reactions of microporous carbon framework under a reducing atmosphere ( Supplementary Figure S1 ) [ 40 , 41 , 42 , 43 ]. The peaks at high temperature in the H 2 -TPR profiles of the prepared Pd catalysts were stronger than that of AC, and that was attributed to the dissociation of H 2 being facilitated over Pd nanoparticles and spilled to the surface of AC (i.e., the spillover effect).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples presented a broad peak centered at approximately 640–660 °C. This was ascribed to the thermal instability of AC, which formed gas products such as CH 4 , CO, and CO 2 via the methanation and thermal decomposition reactions of microporous carbon framework under a reducing atmosphere ( Supplementary Figure S1 ) [ 40 , 41 , 42 , 43 ]. The peaks at high temperature in the H 2 -TPR profiles of the prepared Pd catalysts were stronger than that of AC, and that was attributed to the dissociation of H 2 being facilitated over Pd nanoparticles and spilled to the surface of AC (i.e., the spillover effect).…”
Section: Resultsmentioning
confidence: 99%
“…The MS signals of H 2 , CH 4 , CO, and CO 2 were monitored by the m/z ratios of 2, 16, 28, and 44, respectively. Note that the CO and CO 2 were formed by thermal decomposition of AC, while CH 4 was formed by methanation of AC ( Supplementary Figure S1 ) [ 40 , 41 , 42 , 43 ]. The powdered X-ray diffraction (XRD) patterns of the catalysts were recorded using an X’Pert PRO (PANalytical, Netherlands) XRD system with Cu Kα radiation ( λ = 1.5406 Å), in the 2 θ range of 10–80° at a scanning rate of 0.04° s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Ruthenium-based catalysts were identified as a promising material for NH 3 synthesis under milder reaction conditions due to their high catalytic activity [32]. Recent studies showed that the synthesis of NH 3 at pressures below 10 bar and at temperatures between 300 and 400 • C was feasible [33,34], which provided a decrease in energy demand (i.e., for synthesis gas compression). Furthermore, a fast response and a high stability towards the thermal cycling was demonstrated [35].…”
Section: Process Intensification Methodsmentioning
confidence: 99%
“…For the catalysts in the reduced form (Figure 3b), signals derived from Ba(NO 3 ) 2 are not detected. According to the literature reports [33], Ba(NO 3 ) 2 is transformed into amorphous BaO x species under ammonia synthesis reaction conditions. The subsequent reaction of BaO x species with atmospheric CO 2 could cause the formation of BaCO 3 particles (exsitu XRPD measurements for the catalyst samples removed from the ammonia synthesis reactor).…”
Section: Phase Composition Of the Precursors And Catalysts In The Red...mentioning
confidence: 96%